Governments of the world : a student companion - Pious, Richard M., 1944- (New York : Oxford University, 1998)
Includes over 500 articles with information on the politics and government of every country in the world, on political systems, movements, and leaders, and on human rights, wars, international organizations, and related topics
vol. 1. Aden--Imperialism - vol. 2. India--Seychelles - vol. 3. Sierra Leone--Zionism
Includes bibliographical references and index.
Keywords: Comparative government -- Handbooks, manuals, etc. -- Juvenile literature; Comparative government -- Handbooks, manuals, etc; World politics -- Handbooks, manuals, etc